2020
DOI: 10.3389/fgene.2020.562967
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA LINC01094 Promotes the Development of Clear Cell Renal Cell Carcinoma by Upregulating SLC2A3 via MicroRNA-184

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common subtype of RCC. Compelling evidence has highlighted the crucial role of long non-coding RNA (lncRNA) in ccRCC. Our current study aims to explore the regulatory mechanism of LINC01094 in the development of ccRCC. Dual-luciferase reporter experiment verified the targeting relationship among miR-184, LINC01094, and SLC2A3. Furthermore, the interaction between LINC01094 and miR-184 was confirmed by RNA immunoprecipitation (RIP) and RNA pull-down. Biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Chen HY et al have reported that the expression level of LINC01094 was prominently increased in ovarian cancer tissues compared with adjacent normal tissues, and LINC01094 overexpression promoted the viability, migration and invasion of ovarian cancer cells (Chen et al, 2021a). Consistently, LINC01094 was highly expressed in the clear cell renal cell carcinoma compared with adjacent normal tissues, and the LINC01094 overexpression was associated with a poor prognosis for the patients with clear cell renal cell carcinoma (Xu et al, 2020). In present study, we rstly found that the overexpression of LINC01094 was associated with a poor prognosis for GC patients.…”
Section: Discussionsupporting
confidence: 81%
“…Chen HY et al have reported that the expression level of LINC01094 was prominently increased in ovarian cancer tissues compared with adjacent normal tissues, and LINC01094 overexpression promoted the viability, migration and invasion of ovarian cancer cells (Chen et al, 2021a). Consistently, LINC01094 was highly expressed in the clear cell renal cell carcinoma compared with adjacent normal tissues, and the LINC01094 overexpression was associated with a poor prognosis for the patients with clear cell renal cell carcinoma (Xu et al, 2020). In present study, we rstly found that the overexpression of LINC01094 was associated with a poor prognosis for GC patients.…”
Section: Discussionsupporting
confidence: 81%
“…Silencing lncRNA plasmacytoma variant translocation 1 suppressed OC cell proliferation, migration and invasion (44). Moreover, inhibiting LINC01094 attenuated proliferation, migration and invasion of ccRCC cells (17). LINC01094 overexpression promoted the proliferation and motility of glioma cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of LINC01094 increased radiosensitivity of ccRCC cells through the microRNA (miR/miRNA)-577/checkpoint kinase 2/forkhead box M1 axis (18). Reports showed that LINC01094 and solute carrier family 2 member 3 (SLC2A3) were highly expressed, while miR-184 was lowly expressed, in ccRCC; LINC01094 regulated SLC2A3 by sponging miR-184, and affected the proliferation, migration and invasion of ccRCC cells (17). Analysis of the Gene Expression Profiling Interactive Analysis (GEPIA) database indicated that LINC01094 was significantly increased in OC (19), but its functional role in OC remained unclear.…”
Section: Linc01094 Promotes the Invasion Of Ovarian Cancer Cells And Regulates The Wnt/β-catenin Signaling Pathway By Targeting Mir-532-3mentioning
confidence: 99%
See 1 more Smart Citation
“…MIR3142HG is a critical regulator of the inflammatory response, and the attenuated expression of MIR3142HG/miR-146a contributes to the reduced inflammatory response in IPF fibroblast ( Hadjicharalambous et al, 2018 ). As for LINC01094, several studies reported that it is a pro-tumorigenic lncRNA, and microRNA-184 ( Xu H. et al, 2020 ), miR-126-5p ( Li and Yu, 2020 ), miR-577 ( Xu J. et al, 2020 ), miR-330-3p ( Zhu et al, 2020 ), and miR-224-5p ( Jiang et al, 2020 ) were identified as its targets. The role of ABALON, AC004009-2, and LINC01711 has not been explored by biological assays, providing directions and clues for future research.…”
Section: Discussionmentioning
confidence: 99%